Six new species of Tipula (Vestiplex) Bezzi (Diptera, Tipulidae) from Tibet - Yang, Qi-cheng; Li, Yan; Pan, Zhao-hui; Liu, Xiao-yan; Yang , Ding (European Journal of Taxonomy, 2021)
Twelve species of the subgenus Vestiplex (Diptera, Tipulidae) were previously known to occur in Tibet (= Xizang), China. Here, six species are described and illustrated as new to science: Tipula (Vestiplex) bucera sp. nov., Tipula (Vestiplex) magatama sp. nov., Tipula (Vestiplex) motuoensis sp. nov., Tipula (Vestiplex) nayogabuensis sp. nov., Tipula (Vestiplex) platyphylla sp. nov. and Tipula (Vestiplex) uncinella sp. nov. The following three species are redescribed: Tipula (Vestiplex) himalayensis Brunetti, 1911, Tipula (Vestiplex) nigroapicalis Brunetti, 1911 and Tipula (Vestiplex) zayulensis Alexander, 1963. A key to the species of Tipula (Vestiplex) from Tibet is presented.